2023
DOI: 10.1097/mpg.0000000000003740
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Assessment of Pediatric Inflammatory Bowel Disease Presentation in NYC During COVID-19

Abstract: Inflammatory bowel disease (IBD) pathogenesis is thought to be induced by a mix of genetic susceptibility, microbial populations, and immune triggers such as infections. Severe acute respiratory syndrome coronavirus 2 (SARS-nCoV2) may have increased capacity to generate autoimmune disease as evidenced by known spikes in diseases such as type 1 diabetes mellitus. Public health interventions like masking and closures additionally created remarkable drops in typical viral infections, with remarkable shifts in inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…There are only a few reported cases of adult patients who developed IBD following COVID-19 and 2 case reports of pediatric patients who developed new-onset Crohn disease, including 1 with concurrent multi-inflammatory syndrome in children ( 7 ). Finally, this case series confirms epidemiological assessments of IBD in New York City that have suggested a link between COVID-19 and UC ( 8 ).…”
Section: Discussionsupporting
confidence: 85%
“…There are only a few reported cases of adult patients who developed IBD following COVID-19 and 2 case reports of pediatric patients who developed new-onset Crohn disease, including 1 with concurrent multi-inflammatory syndrome in children ( 7 ). Finally, this case series confirms epidemiological assessments of IBD in New York City that have suggested a link between COVID-19 and UC ( 8 ).…”
Section: Discussionsupporting
confidence: 85%
“…This increase coincided with the onset of the COVID-19 pandemic. Similar trends were observed in the study from Ashton et al [14] from the south of England and Rosenbaum et al [15] from New York City (NYC), both reporting a rise in incidence at the beginning of the 2020 pandemic. These findings prompt inquiries into the potential association between viral illnesses, particularly SARS-CoV-2, and the pathogenesis of IBD.…”
Section: Incidence Of Ibdsupporting
confidence: 80%
“…A US study with data on 587 pediatric IBD cases showed an increased incidence of pediatric IBD diagnoses during the COVID-19 pandemic compared to the expected number based on historic time trend data. 144 In contrast, the most extensive study of some 4300 IBD patients reported a lower risk of incident IBD following SARS-CoV-2 compared to a propensity-score matched cohort who tested negative for SARS-CoV-2 (RR 0.63; 95% CI: 0.58–0.70). 122 The lower IBD incidence post-COVID remained essentially unchanged when restricted to IBD diagnosed >6 months after testing for COVID-19.…”
Section: Ibdmentioning
confidence: 96%